(3HOGjI GdeMJGL aj TQM GdefgGLs - (3eMeO Hf CHj HcQ Hf CMeO Hf eMeO, CHh GdaVd, HOQ GdOjf GdCSOj GdTGaYqj, GdeYQha cSdag HGHf bGVj TgHI , (B874 (3g` s; (3Gdfhhj,J (B676 (3g` s ((3MdH s)
(3ChdgG (B:s
(3jHOC HcJGH GdhUGjG s
(3BNQgG (B:s
(3jfJgi HcJGH (B" (3CegGJ GdChdGO (B" s
(3GdfSNI HgG MhGTs
(3cJH GdeJf HGdMeQIs
(3Ydi ghGeTgG JbjjOGJ hJUMjMGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdTGaYjs